Biofilm formation and microbial quality monitoring in a decentralized greywater collection and treatment system - Zoghbor, Khamees (My University, 2021)
With the emerging of water scarcity problems resulted from increasing population and urbanization, reutilized greywater is considered one of the most promising alternative sources that contributes to alleviate stress on municipal drinking water supplies. An onsite decentralized greywater reuse system was installed in a living lab in Gothenburg, Sweden (HSB living lab, HLL) collecting greywater from bathroom sinks and showers in six shared bathrooms. The produced greywater pass through four treatment processes including ultrafiltration, activated carbon filter, ion exchange filter and advanced oxidation processes which produce high quality water intended to be reused for showering as hot water in two shared bathrooms. Although the available greywater treatment processes remove the majority of microorganisms and organic materials in raw greywater, the produced water is still not sterile and low level of microorganisms may survive and persist when entering the storage tanks. 90% of the total microorganisms in water can be found in biofilms while only 5% can be found as floating planktonic cells in water. The objective of this thesis is to monitor biofilm formation and microbial quality in storage tanks for four weeks under different conditions to ensure the microbial stability of produced water in the tanks in order to not posing any health risks to the users. Therefore, a sampling campaign was conducted to monitor the water microbial qualityparameters such as indicator bacteria (total coliforms, E. coli), L. Pneumophila, biofilm formation as well as the water characteristics such as physical parameter, organic and inorganic nutrients concentrations. The results shows that there is no microbial quality deterioration observed throughout the study under different conditions (different temperatures, different surface materials, water stagnation) since no L. Pneumophila, coliforms and E. coli growth or biofilm formed throughout the study. The results of this study should be viewed as a start point for a long-term monitoring to ensure continuous providing of safe water for showering.
Keywords: water reuse; L. pneumophila; decentralized greywater systems; greywater microbial quality; greywater reuse